Comparison of attention span between different years of a medical college - Hurmat Fatima Bhatti; Maham Tahir; Mahnoor Fayyaz; Ali Tahir; Abdullah Aftab; Naila Azam; Mehwish Riaz (Journal of the Pakistan Medical Association, 2025)
Objectives: To determine the association between attention span and the academic year among medical students, and to identify the factors affecting the attention span. Method: The cross-sectional study at the Foundation University Medical College, Islamabad, Pakistan, from July to August 2022, and comprised medical students from 1st to 5th academic year. Data was collected using the online Attention Control Scale questionnaire. Data was analysed using SPSS 26. Results: Of the 285 subjects with mean age 21.1+1.68 years, 195(68.4%) were females and 90(31.6%) were males. The mean score among the males was 50.31±6.37 compared to 48.12±7.12 for the females. Third-year students had the lowest mean score 46.67±7.02, while fourth-year students scored the highest 49.98±6.67. Significantly influenced internal factors were emotions about 154(54.7%), while longer courses 196(68.8%) and nearby noises 118 (41.4%) were additional factors. Finally, 204(71.6%) students struggled while listening to a one-hour class, and 148 (52.28%) preferred problem-based learning and small group discussions as teaching methods. Conclusion: Traditional lectures and long group discussions affected students' attention span negatively, with external factors, like course length and loud surroundings, and internal factors, like emotions and learner type, having an influence. Key Words: Attention span, Internal and external factors.